Analisis Keterlibatan Gereja Lopomaus Bone dalam Menghadapi Tantangan Adat dan Spiritual Kontemporer pada Generasi Muda (Jurnal Pendidikan Agama dan Teologi, 2025)
This article analyzes the dynamics of the relationship between customs and the church in Bone Village, particularly the GMIT Jemaat Lopomaus Bone Church, in facing contemporary spiritual challenges, as well as its impact on the faith development of young people. Using a mixed-method research approach, data was collected through in-depth interviews with customary leaders, church leaders, representatives of parents, and youth leaders, as well as participatory observation. The research findings indicate that there has been strong harmony and collaboration between customs and the church since the arrival of Christianity, which contributes to the resolution of social issues and cultural preservation through social media. However, the nurturing of young people's faith faces significant obstacles such as the lack of special church programs, limited human resources (HR) in understanding faith, and the absence of a permanent pastor. Youth initiatives and support from teachers in 2023 have become turning points that drive the participation of parents and the congregation. This article recommends the need for an increase in structured faith development programs, strengthening of human resources, and serious efforts to have a permanent pastor to optimize the role of the church in shaping the spirituality of the younger generation in the midst of strong customary traditions.